A Companion to Andrei Platonov's "The Foundation Pit" Studies in Russian and Slavic Literatures, Cultures and History - Seifrid, Thomas (Studies in Russian and Slavic Literatures, Cultures, and History, 2009)
Written at the height of Stalin's first "five-year plan" for the industrialization of Soviet Russia and the parallel campaign to collectivize Soviet agriculture, Andrei Platonov's The Foundation Pit registers a dissonant mixture of utopian longings and despair. Furthermore, it provides essential background to Platonov's parody of the mainstream Soviet "production" novel, which is widely recognized as one of the masterpieces of twentieth-century Russian prose. In addition to an overview of the work's key themes, it discusses their place within Platonov's oeuvre as a whole, his troubled relations with literary officialdom, the work's ideological and political background, and key critical responses since the work's first publication in the West in 1973.